1992
DOI: 10.1111/j.1476-5381.1992.tb14466.x
|View full text |Cite
|
Sign up to set email alerts
|

MDL 26,479: a potential cognition enhancer with benzodiazepine inverse agonist‐like properties

Abstract: 1 The present study investigated biochemical, electrophysiological and behavioural properties of the novel cognition enhancer, MDL 26,479 (5-(3-fluorophenyl)-2,4,-dimethyl-3H-1,2,4-triazole-3-thione). 2 The 5-aryl-1,2,4-triazole, MDL 26,479, potently (0.22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…[29][30][31][32] As BZR and neurons measured by FMZ or IMZ are preserved in the early stages of AD, the patients may be treatable with those cognition enhancers having benzodiazepine inverse agonist-like properties. [21][22][23][24][25][26][27][28][29][30][31] It is also suggested that benzodiazepines may have protective effects against AD based on epidemiological evidence of an association between benzodiazepine use and the occurrence of AD and vascular dementia in 668 individuals. 43 The in vivo measurement of density of BZR may provide the indication of the drug medication for AD patients.…”
Section: Benzodiazepine Receptor In Alzheimermentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32] As BZR and neurons measured by FMZ or IMZ are preserved in the early stages of AD, the patients may be treatable with those cognition enhancers having benzodiazepine inverse agonist-like properties. [21][22][23][24][25][26][27][28][29][30][31] It is also suggested that benzodiazepines may have protective effects against AD based on epidemiological evidence of an association between benzodiazepine use and the occurrence of AD and vascular dementia in 668 individuals. 43 The in vivo measurement of density of BZR may provide the indication of the drug medication for AD patients.…”
Section: Benzodiazepine Receptor In Alzheimermentioning
confidence: 99%
“…Other investigators reported a more prominent reduction in IMZ uptake than CBF decrease measured by HMPAO in patients with AD. 28 As cognition enhancers in relation to benzodiazepine receptors have been proposed as a treatment of AD, [29][30][31][32] in vivo evaluation of BZR is becoming more important.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have provided evidence for the beneÞcial behavioral e¤ects of benzodiazepine receptor weak or selective inverse agonists in humans and animals pretreated with scopolamine (Duka et al 1987;Kumar et al 1988;Deacon et al 1990;Holley et al 1992;Mazurkiewicz et al 1992;Miller et al 1992;Prather et al 1992). ZK93426 (ethyl-5-isopropoxy-4-methyl-6-carboline-3-carboxylate), which possesses more inverse agonist activity than RO 15-1788 has been shown to enhance attentional abilities in human volunteers tested with a logical reasoning task and a picture-di¤erences task.…”
Section: Discussionmentioning
confidence: 97%
“…MDL 26479 (Suritozole) is a negative modulator at GABA A receptors. This drug is similar to other benzodiazepine (BZD) receptor inverse agonists, however it lacks proconvulsive or axiogenic properties [85]. Previous research has shown that MDL 26479 increases cholinergic transmission and enhances cognition in animals [86,87].…”
Section: Gamma-aminobutyric Acid (Gaba) Systemmentioning
confidence: 97%
“…This would support previous work that shows beneficial effects of cholinergic agonists on cognitive outcome after TBI. Importantly, MDL 26479 may also affect other neurotransmitters systems and be influential in long-term potentiation (LTP) [85]. In remains unclear as to whether MDL 26479 did not attenuate cognitive deficits in the delayed administration group because of the delayed postinjury interval or fewer total drug injections.…”
Section: Gamma-aminobutyric Acid (Gaba) Systemmentioning
confidence: 99%